Private Rechtsdurchsetzung des Kartellrechts aus rechtsvergleichender Sicht: Europäische Union, Deutschland und China - Xiao, Yukun (Münchener Schriften zum Europäischen und Internationalen Kartellrecht, 2023)
Private enforcement of competition law should focus not only on damages and compensation but also on deterrence as an equal objective. The book provides an in-depth comparison of law and practice in the EU, Germany, and China, illustrating the different but complementary roles of nullity of restrictive agreements, injunctive relief, and damages actions in private enforcement. It concludes with approaches for enhancing private enforcement within a dual-goal framework and suggests targeted improvements for Chinese competition law enforcement. The book provides valuable insights into judicial practice and the recent amendment of China's Antimonopoly law.